Application of "oil-phase" microbes to enhance oil recovery in extra heavy oil reservoir with high water-cut: A proof-of-concept study. (19th March 2023) - Hao, Li-Hui; Chi, Chang-Qiao; Luo, Na; Nie, Yong; Tang, Yue-Qin; Wu, Xiao-Lei
Abstract: Microbial enhanced oil recovery (MEOR) is an important tertiary recovery technology to recover oil, especially heavy oil, from reservoirs. However, MEOR often fails to achieve satisfactory oil recovery in the field applications because of utilization of unsuitable microorganisms and nutrients. Recent studies proved the existence of microbes inside oil ("oil-phase" microbes) and their potential for application in MEOR. To validate this concept, we isolated microbes from the "oil-phase" of crude oil samples. With them, a synthetic four-member microbial consortium K, was selected to use in an experiment of core flooding, which showed a beneficial capacity for improving oil recovery. Furthermore, the consortium K and nutrients were applied in a field trial of microbial huff and puff in an extra heavy oil recovery. Results demonstrated the incremental cumulative oil production of two high water-cut (99%) shut-in wells reached 1078.8 t and 791.6 t, respectively, with the effective period of 14 months, while the viscosity of heavy oil had significantly declined decreased by 50%. In conclusion, our findings clearly demonstrate that the great potential of a novel methodology to use indigenous "oil-phase" microbes as seedbanks for improving oil recovery in extremely viscous oil reservoirs with high water-cut.